2022
DOI: 10.1186/s12909-022-03756-2
|View full text |Cite
|
Sign up to set email alerts
|

Students’ learning experiences of three-dimensional printed models and plastinated specimens: a qualitative analysis

Abstract: Background Traditional cadaveric dissection is declining whilst plastinated and three-dimensional printed (3DP) models are increasingly popular as substitutes to the conventional anatomy teaching and learning methods. It is unclear about the pros and cons of these new tools and how they impact students’ learning experiences of anatomy including humanistic values such as respect, care and empathy.  Methods Ninety-six students’ views were sought imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 62 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…According to student perceptions, there were mixed opinions about the motivation to learn anatomy with plastinates. This could be because of the absence of real tactile feedback and emotional engagement when using only plastinated materials, as well as a less dynamic exploration compared to standard donor dissection 14,45 . The fourth theme, integration of plastinated specimens with other tools, highlighted the benefits of multi‐modal anatomy instruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to student perceptions, there were mixed opinions about the motivation to learn anatomy with plastinates. This could be because of the absence of real tactile feedback and emotional engagement when using only plastinated materials, as well as a less dynamic exploration compared to standard donor dissection 14,45 . The fourth theme, integration of plastinated specimens with other tools, highlighted the benefits of multi‐modal anatomy instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Ease of use and handling Plastinated specimens were informative, highly valuable, and useful 38,41,45 Plastic models were easiest to handle, followed by plastinated specimens and cadavers 45 Plastinated specimens were easier to handle than cadavers, 41 but wax models were even easier 38 Motivation to learn anatomy Varied effect of plastinated specimens on student motivation to study anatomy 14,41,45 Plastinated specimens inspired most students to learn anatomy after engaging with them 14 Spatial understanding and structure identification Plastinated specimens enabled structure identification and enhanced spatial understanding. 26,41,47 3D models were helpful to students compared to plastinated specimens 43 Plastinated and wet specimens are superior to plastic models for structure recognition 45 Plastinated specimens helped them visualize scans in 3D visualization 39 Student learning preferences Students favored a multi-modal approach to anatomy learning 26,37,45 Plastinated specimens were highly favored for their practicability, usefulness, and learning efficacy 45 Integration of plastinated specimens with cadavers was found to be more effective for learning 14,46 Preferences for learning modalities varied, including cadavers, plastinated, small group seminars, 3D-printed models, textbooks, wax models, and photographs 2,38,42,47 constraints by novice learners and, as such, are more likely to result in damaged or imperfect specimens, limiting students' abilities to fully appreciate the anatomy. 41 These limitations are especially evident when learning the head and neck; one of the most complex and difficult areas for less experienced learners to dissect.…”
Section: Theme(s) Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissection could also play an important role in PIF through reinforcing compassion and respectful attitudes [ 22 , 23 ] and patient-centered professionalism [ 24 ] as seen in various qualitative research using oral [ 25 ] and written reflections [ 2 , 25 ] as well as surveys questionnaire [ 26 ]. Interestingly, a study also showed students perceived plastinated specimens with more respect and care than three-dimensional printed models as they recognised the specimens as more real and authentic [ 27 ]. In this manner, dissection providing the real hands-on experience with the human body can be useful in enhancing students’ appreciation and respect, which are part of the process of PIF.…”
Section: Introductionmentioning
confidence: 99%
“…Desde o século XVII, o estudo da Anatomia Humana baseia-se na prática de dissecação de cadáveres. No entanto, os elevados custos para a preservação dos corpos e dos laboratórios associados, bem como, as questões éticas envolvendo a baixa doação de corpos levaram à procura de novas alternativas de ensino (Radzi et al, 2022). Com o avanço da tecnologia da indústria nos últimos anos e sua inserção junto aos cursos de Saúde, novos dispositivos digitais surgiram no intuito de melhorar a prestação de cuidados à Saúde; destacando-se a adoção da impressão 3D nas escolas médicas, a qual cresceu de modo importante nos últimos 5 anos (Wickramasinghe et al, 2022).…”
Section: Introductionunclassified